Cardiac T2 star mapping: standardized inline analysis of long and short axis at three identical 1.5 T MRI scanners - Heiß, Rafael; Wiesmüller, Marco; Treutlein, Christoph; Seuß, Hannes; Uder, Michael; May, Matthias; Wüst, Wolfgang (International Journal of Cardiovascular Imaging, 2019)
T2 star mapping can be applied for in vivo cardiac iron quantification. Current recommendations of imaging acquisition, post-processing and interpretation of normal values are based on old scanner types and in house software packages. A standardized comparison of short (SAX) and long axis (LAX) segments using commercially available software packages and modern scanners is lacking. To provide a standardized comparison of T2 star time values in SAX and LAX and to investigate intersegmental, interregional and inter-level comparison and the interscanner reproducibility. 84 cardiac MRIs in 28 healthy volunteers were performed with three structurally identical 1.5 T MRI scanners. A commercially available software package for T2 star mapping with automatic in-line motion correction was used for analysis. Regions of interest were manually placed in each of the 16 myocardial segments according to the AHA model in three SAX and three LAX. A total of 2856 ROIs were drawn and 102 segments per volunteer were analysed. Interscanner reproducibility was high (91%) and the mean myocardial T2 star time value for all evaluated segments was 34 ± 5.7 ms. No significant difference was found between all measurements in SAX (35 ± 5.5 ms) and LAX (34 ± 5.8 ms). T2 star time values varied significantly between heart segments in the same axis and in 44% between corresponding SAX and LAX segments. T2 star time values in SAX and LAX have a high interscanner reproducibility but can vary significantly between heart segments in the same axis. Comparability between corresponding SAX and LAX segments is limited. To get representative results T2 star time values should be obtained in more than one heart segment and for follow-up studies identical segments should be used to avoid a systematic bias.
EVALuna2:210886

Computer-aided evaluation of low-dose and low-contrast agent third-generation dual-source CT angiography prior to transcatheter aortic valve implantation (TAVI) - Dankerl, Peter; Hammon, Matthias; Seuß, Hannes; Tröbs, Monique; Schuhbaeck, Annika; Hell, Michaela M.; Achenbach, Stephan; Uder, Michael; Marwan, Mohamed; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2016)
To evaluate the performance of computer-aided evaluation software for a comprehensive workup of patients prior to transcatheter aortic valve implantation (TAVI) using low-contrast agent and low radiation dose third-generation dual-source CT angiography.We evaluated 30 consecutive patients scheduled for TAVI. All patients underwent ECG-triggered high-pitch dual-source CT angiography of the aortic root and aorta with a standardized contrast agent volume (30 ml Imeron350, flow rate 4 ml/s) and low-dose (100 kv/350 mAs) protocol. An expert (10 years of experience) manually evaluated aortic root and iliac access dimensions (distance between coronary ostia and aortic annulus, minimal/maximal diameters and area-derived diameter of the aortic annulus) and best CT-predicted fluoroscopic projection angle as the reference standard. Utilizing computer-aided software (syngo.via), the same pre-TAVI workup was performed and compared to the reference standard.Mean CTDI[Formula: see text] was 3.46 mGy and mean DLP 217.6 ± 12.1 mGy cm, corresponding to a mean effective dose of 3.7 ± 0.2 mSv. Computer-aided evaluation was successful in all but one patient. Compared to the reference standard, Bland-Altman analysis indicated very good agreement for the distances between aortic annulus and coronary ostia (RCA: mean difference 0.8 mm; 95 % CI 0.4-1.2 mm; LM: mean difference 0.9 mm; 95 % CI 0.5-1.3 mm); however, we demonstrated a systematic overestimation of annulus- derived diameter using the software (mean difference 44.4 mm[Formula: see text]; 95 % CI 30.4-58.3 mm[Formula: see text]). Based on respective annulus dimensions, the recommended prosthesis size (Edwards SAPIEN 3) matched in 26 out of the 29 patients (90 %). CT-derived fluoroscopic projection angles showed an excellent agreement for both methods. Out of 58 iliac arteries, 15 (25 %) arteries could not be segmented by the software. Preprocessing time of the software was 71 ± 11 s (range 51-96 s), and reading time with the software was 118 ± 31 s (range 68-201 s).In the workup of pre-TAVI CT angiography, computer-aided evaluation of low-contrast, low-dose examinations is feasible with good agreement and quick reading time. However, a systematic overestimation of the aortic annulus area is observed.
EVALuna2:14602

Daratumomab for the treatment of relapsed multiple myeloma involving the central nervous system: a case report - Brandt, Adrian; Seuß, Hannes; Mackensen, Andreas; Rösler, Wolf (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Development and Evaluation of a Semi-automated Segmentation Tool and a Modified Ellipsoid Formula for Volumetric Analysis of the Kidney in Non-contrast T2-Weighted MR Images - Seuß, Hannes; Janka, Rolf Matthias; Pruemmer, Marcus; Hammon, Rebecca; Theis, Ragnar; Sandmair, Martin; Amann, Kerstin Ute; Bäuerle, Tobias; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Journal of Digital Imaging, 2017)
Volumetric analysis of the kidney parenchyma provides additional information for the detection and monitoring of various renal diseases. Therefore the purposes of the study were to develop and evaluate a semi-automated segmentation tool and a modified ellipsoid formula for volumetric analysis of the kidney in non-contrast T2-weighted magnetic resonance (MR)-images. Three readers performed semi-automated segmentation of the total kidney volume (TKV) in axial, non-contrast-enhanced T2-weighted MR-images of 24 healthy volunteers (48 kidneys) twice. A semi-automated threshold-based segmentation tool was developed to segment the kidney parenchyma. Furthermore, the three readers measured renal dimensions (length, width, depth) and applied different formulas to calculate the TKV. Manual segmentation served as a reference volume. Volumes of the different methods were compared and time required was recorded. There was no significant difference between the semi-automatically and manually segmented TKV (p = 0.31). The difference in mean volumes was 0.3 ml (95% confidence interval (CI), -10.1 to 10.7 ml). Semi-automated segmentation was significantly faster than manual segmentation, with a mean difference = 188 s (220 vs. 408 s); p < 0.05. Volumes did not differ significantly comparing the results of different readers. Calculation of TKV with a modified ellipsoid formula (ellipsoid volume × 0.85) did not differ significantly from the reference volume; however, the mean error was three times higher (difference of mean volumes -0.1 ml; CI -31.1 to 30.9 ml; p = 0.95). Applying the modified ellipsoid formula was the fastest way to get an estimation of the renal volume (41 s). Semi-automated segmentation and volumetric analysis of the kidney in native T2-weighted MR data delivers accurate and reproducible results and was significantly faster than manual segmentation. Applying a modified ellipsoid formula quickly provides an accurate kidney volume.
EVALuna2:14622

Dynamic CT angiography for therapy evaluation after transarterial chemoembolization of hepatocellular carcinoma - Saake, Marc; Seuß, Hannes; Hammon, Matthias; Ellmann, Stephan; May, Matthias; Uder, Michael; Schmid, Axel (Acta Radiologica, 2019)
Background: Liver dynamic computed tomography (CT) is an established method for pre- and post-interventional evaluation of hepatocellular carcinoma. To date only the liver parenchyma and perfusion information of dynamic CT has been evaluated widely. Purpose: To evaluate the vascular information contained in dynamic CT datasets. Material and Methods: Dynamic CT performed one day after transarterial chemoembolization (60 mL of contrast medium, 6 mL/s, 40 s scan duration) were retrospectively evaluated. Conventional slice and angiographic maximum-intensity-projection reconstructions were calculated on a multi-modality post-processing platform. Datasets were evaluated for viable tumor, anatomy of the vasculature, and potential tumor-feeding vessels. The results were compared to digital subtraction angiography images. Results: In total, 94 treated hepatocellular carcinoma nodules were evaluated (62 dynamic CT scans, 46 patients [34 men; mean age = 69 years]). Forty-six partially viable tumors were diagnosed after transarterial chemoembolization. In all of these, tumor-feeding vessels were found in dynamic CT. Seventeen suspected extra-hepatic tumor feeders were reported, of which 14 had not been found during previous transarterial chemoembolization. Conclusion: Dynamic CT is useful in post-interventional imaging of hepatocellular carcinoma after transarterial chemoembolization due to its ability to detect residual viable tumor parts and to show previously unknown intra- and extra-hepatic tumor-feeding vessels.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Abdomen; chemoembolization; computed tomography angiography; interventional; liver

Evaluation of Rib Fractures on a Single-in-plane Image Reformation of the Rib Cage in CT Examinations - Dankerl, Peter; Seuß, Hannes; Ellmann, Stephan; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Academic Radiology, 2016)
This study aimed to evaluate the diagnostic performance of using a reformatted single-in-plane image reformation of the rib cage for the detection of rib fractures in computed tomography (CT) examinations, employing different levels of radiological experience.We retrospectively evaluated 10 consecutive patients with and 10 patients without rib fractures, whose CT scans were reformatted to a single-in-plane image reformation of the rib cage. Eight readers (two radiologists, two residents in radiology, and four interns) independently evaluated the images for the presence of rib fractures using a reformatted single-in-plane image and a multi-planar image reformation. The time limit was 30 seconds for each read. A consensus of two radiologist readings was considered as the reference standard. Diagnostic performance (sensitivity, specificity, positive predictive value [PPV], and negative predictive value [NPV]) was assessed and evaluated per rib and per location (anterior, lateral, posterior). To determine the time limit, we prospectively analyzed the average time it took radiologists to assess the rib cage, in a bone window setting, in 50 routine CT examinations. McNemar test was used to compare the diagnostic performances.Single image reformation was successful in all 20 patients. The sensitivity, specificity, PPV, and NPV for the detection of rib fractures using the conventional multi-planar read were 77.5%, 99.2%, 89.9%, and 98.0% for radiologists; 46.3%, 99.7%, 92.5%, and 95.3% for residents; and 29.4%, 99.4%, 82.5%, and 93.9% for interns, respectively. Sensitivity, PPV, and NPV increased across all three groups of experience, using the reformatted single-in-plane image of the rib cage (radiologists: 85.0%, 98.6%, and 98.7%; residents: 80.0%, 92.8%, and 98.2%; interns: 66.9%, 89.9%, and 97.1%), whereas specificity did not change significantly (99.9%, 99.4%, and 99.3%). The diagnostic performance of the interns and residents was significantly better when evaluating the single-in-plane image reformations (P < .01). The diagnostic performance of the radiologists was better when evaluating the single-in-plane image reformations; however, there was no significant difference (statistical power: 0.32).The diagnostic performance for the detection of rib fractures, using CT images that have been reformatted to a single-in-plane image, improves for readers from different educational levels when the evaluation time is restricted to 30 seconds or less.
EVALuna2:14593

Feature-guided deep learning reduces signal loss and increases lesion CNR in diffusion-weighted imaging of the liver - Führes, Tobit; Saake, Marc; Lorenz, Jennifer; Seuß, Hannes; Bickelhaupt, Sebastian; Uder, Michael; Laun, Frederik Bernd (Zeitschrift für Medizinische Physik, 2023)
Purpose: This research aims to develop a feature-guided deep learning approach and compare it with an optimized conventional post-processing algorithm in order to enhance the image quality of diffusion-weighted liver images and, in particular, to reduce the pulsation-induced signal loss occurring predominantly in the left liver lobe. Methods: Data from 40 patients with liver lesions were used. For the conventional approach, the best-suited out of five examined algorithms was chosen. For the deep learning approach, a U-Net was trained. Instead of learning “gold-standard” target images, the network was trained to optimize four image features (lesion CNR, vessel darkness, data consistency, and pulsation artifact reduction), which could be assessed quantitatively using manually drawn ROIs. A quality score was calculated from these four features. As an additional quality assessment, three radiologists rated different features of the resulting images. Results: The conventional approach could substantially increase the lesion CNR and reduce the pulsation-induced signal loss. However, the vessel darkness was reduced. The deep learning approach increased the lesion CNR and reduced the signal loss to a slightly lower extent, but it could additionally increase the vessel darkness. According to the image quality score, the quality of the deep-learning images was higher than that of the images obtained using the conventional approach. The radiologist ratings were mostly consistent with the quantitative scores, but the overall quality ratings differed among the readers. Conclusion: Unlike the conventional algorithm, the deep-learning algorithm increased the vessel darkness. Therefore, it may be a viable alternative to conventional algorithms.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Cardiac motion artifact; Deep learning; Diffusion; Liver; Neural network; Oncology

Flow-compensated diffusion encoding in MRI for improved liver metastasis detection - Laun, Frederik Bernd; Führes, Tobit; Seuß, Hannes; Müller, Astrid; Bickelhaupt, Sebastian; Stemmer, Alto; Benkert, Thomas; Uder, Michael; Saake, Marc (PLoS ONE, 2022)
Magnetic resonance (MR) diffusion-weighted imaging (DWI) is often used to detect focal liver lesions (FLLs), though DWI image quality can be limited in the left liver lobe owing to the pulsatile motion of the nearby heart. Flow-compensated (FloCo) diffusion encoding has been shown to reduce this pulsation artifact. The purpose of this prospective study was to intra-individually compare DWI of the liver acquired with conventional monopolar and FloCo diffusion encoding for assessing metastatic FLLs in non-cirrhotic patients. Forty patients with known or suspected multiple metastatic FLLs were included and measured at 1.5 T field strength with a conventional (monopolar) and a FloCo diffusion encoding EPI sequence (single refocused; b-values, 50 and 800 s/mm2). Two board-certified radiologists analyzed the DWI images independently. They issued Likert-scale ratings (1 = worst, 5 = best) for pulsation artifact severity and counted the difference of lesions visible at b = 800 s/mm2 separately for small and large FLLs (i.e., < 1 cm or > 1 cm) and separately for left and right liver lobe. Differences between the two diffusion encodings were assessed with the Wilcoxon signed-rank test. Both readers found a reduction in pulsation artifact in the liver with FloCo encoding (p < 0.001 for both liver lobes). More small lesions were detected with FloCo diffusion encoding in both liver lobes (left lobe: six and seven additional lesions by readers 1 and 2, respectively; right lobe: five and seven additional lesions for readers 1 and 2, respectively). Both readers found one additional large lesion in the left liver lobe. Thus, flow-compensated diffusion encoding appears more effective than monopolar diffusion encoding for the detection of liver metastases.
CRIS-Team Scopus Importer:2022-08-05

Image Quality and Detection of Small Focal Liver Lesions in Diffusion-Weighted Imaging Comparison of Navigator Tracking and Free-Breathing Acquisition - Saake, Marc; Seuß, Hannes; Riexinger, Andreas; Bickelhaupt, Sebastian; Hammon, Matthias; Uder, Michael; Laun, Frederik Bernd (Investigative Radiology, 2021)
Objectives The aim of this study was to compare intraindividual diffusion-weighted imaging (DWI) of the liver acquired with free breathing (FB) versus navigator triggering (NT) for assessing small focal liver lesions (FLLs) in noncirrhotic patients. Materials and Methods Patients with known or suspected multiple FLLs were prospectively included, and spin-echo echo-planar DWI with NT and FB acquisition was performed (b-values, 50 and 800 s/mm(2) [b50 and b800]). NT and FB DWI sequences with similar acquisitions times were used. Liver and lesion signal-to-noise ratios were measured at b800. The DWI scans were analyzed independently by 2 readers. Liver edge delineation, presence of stair-step artifacts, vessel sharpness, severity of cardiac motion artifacts, overall image quality, and lesion conspicuity were rated with 5-point Likert scales. Small and large FLLs (ie, <1 cm or >= 1 cm) were rated separately for lesion conspicuity. The FLL detectability was estimated by comparing the number of lesions visible with FB to those visible with NT. Results Forty-three patients were included in the study. The FB acquisition performed better in terms of severity of cardiac motion artifacts. The NT performed better in terms of liver edge delineation and vessel sharpness. Little difference was found for stair-step artifact, overall image quality, and conspicuity of large FLL, whereas the conspicuity of small FLL was better for NT. For small FLL, both readers found more lesions with NT in 11 cases at b800. For large FLL, this effect was much less pronounced (1 case at b800 reported by 1 of the readers). The mean liver and lesion signal-to-noise ratios were 16.8/41.5 and 19.8/38.4 for NT/FB, respectively. Conclusions Small FLL detection is better with NT. Large FLL detection by FB and NT is similarly good. We conclude that NT should be used.
CRIS-Team WoS Importer:2021-09-03

Impact of intelligent virtual and AI-based automated collimation functionalities on the efficiency of radiographic acquisitions - Rasche, A.; Brader, P.; Borggrefe, J.; Seuß, Hannes; Carr, Z.; Hebecker, A.; ten Cate, G. (Radiography, 2024)
Introduction: Intelligent virtual and AI-based collimation functionalities have the potential to enable an efficient workflow for radiographers, but the specific impact on clinical routines is still unknown. This study analyzes primarily the influence of intelligent collimation functionalities on the examination time and the number of needed interactions with the radiography system. Methods: An observational study was conducted on the use of three camera-based intelligent features at five clinical sites in Europe and the USA: AI-based auto thorax collimation (ATC), smart virtual ortho (SVO) collimation for stitched long-leg and full-spine examinations, and virtual collimation (VC) at the radiography system workstation. Two people conducted semi-structured observations during routine examinations to collect data with the functionalities either activated or deactivated. Results: Median exam duration was 31 vs. 45 s (p < 0.0001) for 95 thorax examinations with ATC and 94 without ATC. For stitched orthopedic examinations, 34 were performed with SVO and 40 without SVO, and the median exam duration was 62 vs. 82 s (p < 0.0001). The median time for setting the ortho range – i.e., the time between setting the upper and the lower limits of the collimation field – was 7 vs. 16 s for 39 examinations with SVO and 43 without SVO (p < 0.0001). In 109 thorax examinations with ATC and 112 without ATC, the median number of system interactions was 1 vs. 2 (p < 0.0001). VC was used to collimate in 2.4% and to check the collimation field in 68.5% of 292 observed chest and other examinations. Conclusion: ATC and SVO enable the radiographer to save time during chest or stitched examinations. Additionally, ATC reduces machine interactions during chest examinations. Implications for practice: System and artificial intelligence can support the radiographer during the image acquisition by providing a more efficient workflow.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Acquisition workflow; Artificial intelligence; Digital radiography; Medical imaging; Radiographer; Workforce

Improved visualization of peripherally inserted central catheters on chest radiographs of neonates using fractional multiscale image processing - Hammon, Rebecca A.; Seuß, Hannes; Hammon, Matthias; Grillhoesl, Christian; Heiß, Rafael; Zeilinger, Martin; Bayerl, Nadine; Vuylsteke, Pieter; Wanninger, Friedrich; Schroth, Michael; Uder, Michael; Rompel, Oliver (BMC Medical Imaging, 2019)
BACKGROUND: Peripherally inserted central catheters (PICCs) provide secure intravenous access for the delivery of life-sustaining medications and nutrition. They are commonly used in pediatrics. Confirmation of correct central catheter tip position is crucial. Verification is usually done by a radiograph. The aim of this study is to evaluate the ability of Fractional Multiscale image Processing (FMP) to detect PICC tips on the digital chest radiographs of neonates. METHODS: A total of 94 radiographs of 47 patients were included in the study. 29 patients were male, 18 were female. The mean age of all examined children was 9.2 days (range 0-99 days). In total, six readers (two radiologists, two residents in radiology, one last year medical student, one neonatologist) evaluated 94 unprocessed and catheter-enhanced radiographs using a 5-point Likert scale (1 = poor catheter tip visualization, 5 = excellent catheter tip visualization). Additionally, the two radiologists evaluated the diagnostic confidence for chest pathologies using a 5-point Likert scale (1 = poor diagnostic confidence, 5 = excellent diagnostic confidence). Radiographs were evaluated on a dedicated workstation. RESULTS: In all cases, the catheter-enhanced radiograph rated higher than (n = 471), or equal (n = 93) to, the unprocessed radiograph when visualizing catheter tips. 87% of the catheter-enhanced radiographs obtained a rating of 4 or higher, while only 42% of unprocessed radiographs received 4 or more points. Regarding diagnostic confidence for chest pathologies one radiologist rated two catheter-enhanced radiographs higher than the unprocessed radiographs, while all other 186 evaluations rated the catheter-enhanced radiographs equal to (n = 78) or lower than (n = 108) the unprocessed radiographs. Only 60% of the catheter-enhanced radiographs yielded a diagnostic confidence of 4 or higher, while 90% of the unprocessed images received 4 or more points. CONCLUSION: Catheter-enhanced digital chest radiographs demonstrate improved visualization of low contrast PICC tips in neonates compared to unprocessed radiographs. Furthermore, they enable detection of accompanying chest pathologies. However, definitive diagnosis of chest pathologies should be made on unprocessed radiographs.
EVALuna2:36095

Improved Visualization of Prostate Cancer Using Multichannel Computed Diffusion Images: Combining ADC and DWI - Hammon, Matthias; Saake, Marc; Laun, Frederik Bernd; Heiß, Rafael; Seuss, Nicola; Janka, Rolf Matthias; Cavallaro, Alexander Josef; Uder, Michael; Seuß, Hannes (Diagnostics, 2022)
(1) Background: For the peripheral zone of the prostate, diffusion weighted imaging (DWI) is the most important MRI technique; however, a high b-value image (hbDWI) must always be evaluated in conjunction with an apparent diffusion coefficient (ADC) map. We aimed to unify the important contrast features of both a hbDWI and ADC in one single image, termed multichannel computed diffusion images (mcDI), and evaluate the values of these images in a retrospective clinical study; (2) Methods: Based on the 2D histograms of hbDWI and ADC images of 70 patients with histologically proven prostate cancer (PCa) in the peripheral zone, an algorithm was designed to generate the mcDI. Then, three radiologists evaluated the data of 56 other patients twice in three settings (T2w images +): (1) hbDWI and ADC; (2) mcDI; and (3) mcDI, hbDWI, and ADC. The sensitivity, specificity, and inter-reader variability were evaluated; (3) Results: The overall sensitivity/specificity were 0.91/0.78 (hbDWI + ADC), 0.85/0.88 (mcDI), and 0.97/0.88 (mcDI + hbDWI + ADC). The kappa-values for the inter-reader variability were 0.732 (hbDWI + ADC), 0.800 (mcDI), and 0.853 (mcDI + hbDWI + ADC). (4) Conclusions: By using mcDI, the specificity of the MRI detection of PCa was increased at the expense of the sensitivity. By combining the conventional diffusion data with the mcDI data, both the sensitivity and specificity were improved.
CRIS-Team WoS Importer:2022-08-12

Interobserver and intermodality agreement of standardized algorithms for non-invasive diagnosis of hepatocellular carcinoma in high-risk patients: CEUS-LI-RADS versus MRI-LI-RADS - Schellhaas, Barbara; Hammon, Matthias; Strobel, Deike; Pfeifer, Lukas; Kielisch, Christian; Görtz, Rüdiger; Janka, Rolf Matthias; Neurath, Markus; Uder, Michael; Seuß, Hannes; Cavallaro, Alexander Josef (European Radiology, 2018)
OBJECTIVES: We compared the interobserver agreement for the recently introduced contrast-enhanced ultrasound (CEUS)-based algorithm CEUS-LI-RADS (Liver Imaging Reporting and Data System) versus the well-established magnetic resonance imaging (MRI)-LI-RADS for non-invasive diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. METHODS: Focal liver lesions in 50 high-risk patients (mean age 66.2 ± 11.8 years; 39 male) were assessed retrospectively with CEUS and MRI. Two independent observers reviewed CEUS and MRI examinations, separately, classifying observations according to CEUS-LI-RADSv.2016 and MRI-LI-RADSv.2014. Interobserver agreement was assessed with Cohen's kappa. RESULTS: Forty-three lesions were HCCs; two were intrahepatic cholangiocarcinomas; five were benign lesions. Arterial phase hyperenhancement was perceived less frequently with CEUS than with MRI (37/50 / 38/50 lesions = 74%/78% [CEUS; observer 1/observer 2] versus 46/50 / 44/50 lesions = 92%/88% [MRI; observer 1/observer 2]). Washout appearance was observed in 34/50 / 20/50 lesions = 68%/40% with CEUS and 31/50 / 31/50 lesions = 62%/62%) with MRI. Interobserver agreement was moderate for arterial hyperenhancement (ĸ = 0.511/0.565 [CEUS/MRI]) and "washout" (ĸ = 0.490/0.582 [CEUS/MRI]), fair for CEUS-LI-RADS category (ĸ = 0.309) and substantial for MRI-LI-RADS category (ĸ = 0.609). Intermodality agreement was fair for arterial hyperenhancement (ĸ = 0.329), slight to fair for "washout" (ĸ = 0.202) and LI-RADS category (ĸ = 0.218) CONCLUSION: Interobserver agreement is substantial for MRI-LI-RADS and only fair for CEUS-LI-RADS. This is mostly because interobserver agreement in the perception of washout appearance is better in MRI than in CEUS. Further refinement of the LI-RADS algorithms and increasing education and practice may be necessary to improve the concordance between CEUS and MRI for the final LI-RADS categorization. KEY POINTS: • CEUS-LI-RADS and MRI-LIRADS enable standardized non-invasive diagnosis of HCC in high-risk patients. • With CEUS, interobserver agreement is better for arterial hyperenhancement than for "washout". • Interobserver agreement for major features is moderate for both CEUS and MRI. • Interobserver agreement for LI-RADS category is substantial for MRI, and fair for CEUS. • Interobserver-agreement for CEUS-LI-RADS will presumably improve with ongoing use of the algorithm.
EVALuna2:34689

Mobile Image Interpretation: Diagnostic Performance of CT Exams Displayed on a Tablet Computer in Detecting Abdominopelvic Hemorrhage - Schlechtweg, Philipp; Kammerer, Ferdinand J.; Seuß, Hannes; Uder, Michael; Hammon, Matthias (Journal of Digital Imaging, 2015)
To investigate whether abdominopelvic hemorrhage shown on computed tomography (CT) images can be diagnosed with the same accuracy on a tablet computer as on a dedicated reading display. One hundred patients with a clinical suspicion of abdominopelvic hemorrhage that underwent biphasic CT imaging were retrospectively read by two readers on a dedicated reading display (reference standard) and on a tablet computer (iPad Air). Reading was performed in a dedicated reading room with ambient light conditions. Image evaluation included signs of an active hemorrhage (extravasation of contrast media) and different signs indicating a condition after abdominopelvic hemorrhage (hematoma, intestinal clots, vessel stump, free abdominopelvic fluid with a mean Hounsfield unit value >20, and asymmetric muscle volume indicating intramuscular hemorrhage). Sensitivity, specificity, and positive and negative predictive values (PPV/NPV) were calculated for the tablet-based reading. Active abdominopelvic hemorrhage (n = 72) was diagnosed with the tablet computer with a sensitivity of 0.96, a specificity of 0.93, a PPV of 0.97, and an NPV of 0.90. The results for the detection of the signs indicating a condition after abdominopelvic hemorrhage range from 0.83 to 1.00 in the case of sensitivity, from 0.95 to 1.00 in the case of specificity, from 0.94 to 1.00 in the case of the PPV, and from 0.96 to 1.00 in the case of the NPV. Abdominopelvic hemorrhage shown on CT images can be diagnosed on a tablet computer with a high diagnostic accuracy allowing mobile on-call diagnoses. This may be helpful because an early and reliable diagnosis at any time is crucial for an adequate treatment strategy.
EVALuna2:14361

On the dependence of the cardiac motion artifact on the breathing cycle in liver diffusion-weighted imaging - Riexinger, Andreas; Laun, Frederik Bernd; Bickelhaupt, Sebastian; Seuß, Hannes; Uder, Michael; Hensel, Bernhard; Saake, Marc (PLoS ONE, 2020)
Purpose The purpose of this study was to investigate whether the cardiac motion artifact that regularly appears in diffusion-weighted imaging of the left liver lobe might be reduced by acquiring images in inspiration, when the coupling between heart and liver might be minimal. Materials and methods 43 patients with known or suspected focal liver lesions were examined at 1.5 T with breath hold acquisition, once in inspiration and once in expiration. Data were acquired with a diffusion-weighted echo planar imaging sequence and two b-values (b50 = 50 s/mm2 and b800 = 800 s/mm2). The severity of the cardiac motion artifact in the left liver lobe was rated by two experienced radiologists for both b-values with a 5 point Likert scale. Additionally, the normalized signal S(b800)/S(b50) in the left liver lobe was computed. The Wilcoxon signed-rank test was used comparing the scores of the two readers obtained in inspiration and expiration, and to compare the normalized signal in inspiration and expiration. Results The normalized signal in inspiration was slightly higher than in expiration (0.349±0.077 vs 0.336±0.058), which would indicate a slight reduction of the cardiac motion artifact, but this difference was not significant (p = 0.24). In the qualitative evaluation, the readers did not observe a significant difference for b50 (reader 1: p = 0.61; reader 2: p = 0.18). For b800, reader 1 observed a significant difference of small effect size favouring expiration (p = 0.03 with a difference of mean Likert scores of 0.27), while reader 2 observed no significant difference (p = 0.62). Conclusion Acquiring the data in inspiration does not lead to a markedly reduced cardiac motion artifact in diffusion-weighted imaging of the left liver lobe and is in this regard not to be preferred over acquiring the data in expiration.
CRIS-Team Scopus Importer:2020-10-16

Osteoblastic lesion screening with an advanced post-processing package enabling in-plane rib reading in CT-images - Seuß, Hannes; Dankerl, Peter; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (BMC Medical Imaging, 2016)
To evaluate screening and diagnostic accuracy for the detection of osteoblastic rib lesions using an advanced post-processing package enabling in-plane rib reading in CT-images.We retrospectively assessed the CT-data of 60 consecutive prostate cancer patients by applying dedicated software enabling in-plane rib reading. Reading the conventional multiplanar reconstructions was considered to be the reference standard. To simulate clinical practice, the reader was given 10 s to screen for sclerotic rib lesions in each patient applying both approaches. Afterwards, every rib was evaluated individually with both approaches without a time limit. Sensitivities, specificities, positive/negative predictive values and the time needed for detection were calculated depending on the lesion's size (largest diameter < 5 mm, 5-10 mm, > 10 mm).In 53 of 60 patients, all ribs were properly displayed in plane, in five patients ribs were partially displayed correctly, and in two patients none of the ribs were displayed correctly. During the 10-s screening approach all patients with sclerotic rib lesions were correctly identified reading the in-plane images (including the patients without a correct rib segmentation), whereas 14 of 23 patients were correctly identified reading conventional multiplanar images. Overall screening sensitivity, specificity, and positive/negative predictive values were 100/27.0/46.0/100 %, respectively, for in-plane reading and 60.9/100/100/80.4 %, respectively, for multiplanar reading. Overall diagnostic (no time limit) sensitivity, specificity, and positive/negative predictive values of in-plane reading were 97.8/92.8/74.6/99.5 %, respectively. False positive results predominantly occurred for lesions <5 mm in size.In-plane reading of the ribs allows reliable detection of osteoblastic lesions for screening purposes. The limited specificity results from false positives predominantly occurring for small lesions.
EVALuna2:14474

Quantitative assessment of muscle injury by (23)Na magnetic resonance imaging - Dahlmann, Anke; Kopp, Christoph; Linz, Peter; Seuß, Hannes; Eckardt, Kai-Uwe; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (SpringerPlus, 2016)
(23)Na magnetic resonance imaging ((23)Na-MRI) is able to measure Na(+) in vivo in humans and allows quantification of tissue sodium distribution. We now tested the utility of (23)Na-MRI technique in detecting and assessing sports-related acute muscular injury.We assessed tissue Na(+) of both lower legs with a 3T MRI scanner using a customized (23)Na knee coil. The affected left calf muscle in an injured volleyball player showed a hyperintense Na(+) signal. Follow-up measurements revealed persistently increased muscle Na(+) content despite complete clinical recovery.Our findings suggest that (23)Na-MRI could have utility in detecting subtle muscular injury and might indicate when complete healing has occurred. Furthermore, (23)Na-MRI suggests the presence of substantial injury-related muscle electrolyte shifts that warrant more detailed investigation.
EVALuna2:3865

Reduction of the cardiac pulsation artifact and improvement of lesion conspicuity in flow-compensated diffusion images in the liver-A quantitative evaluation of postprocessing algorithms - Führes, Tobit; Saake, Marc; Lorenz, Jennifer; Seuß, Hannes; Stemmer, Alto; Benkert, Thomas; Uder, Michael; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2022)
Purpose To enhance image quality of flow-compensated diffusion-weighted liver MRI data by increasing the lesion conspicuity and reducing the cardiac pulsation artifact using postprocessing algorithms. Methods Diffusion-weighted image data of 40 patients with liver lesions had been acquired at 1.5 T. These data were postprocessed with 5 different algorithms (weighted averaging, p-mean, percentile, outlier exclusion, and exception set). Four image properties of the postprocessed data were evaluated for optimizing the algorithm parameters. These properties were the lesion to tissue contrast-to-noise ratio (CNR), the reduction of the cardiac pulsation artifact, the data consistency, and the vessel darkness. They were combined into a total quality score ( set to 1 for the trace-weighted reference image), which was used to rate the image quality objectively. Results The weighted averaging algorithm performed best according to the total quality score (). The further ranking was outlier exclusion algorithm (), p-mean algorithm (), percentile algorithm (), and exception set algorithm (). All optimized algorithms except for the exception set algorithm corrected the pulsation artifact and increased the lesion CNR. Changes in were significant for all optimized algorithms except for the percentile algorithm. Liver ADC was significantly reduced (except for the exception set algorithm), particularly in the left lobe. Conclusion Postprocessing algorithms should be used for flow-compensated liver DWI. The proposed weighted averaging algorithm seems to be suited best to increase the image quality of artifact-corrupted flow-compensated diffusion-weighted liver data.
CRIS-Team WoS Importer:2022-09-23

Reproducibility of Kidney Perfusion Measurements With Arterial Spin Labeling at 1.5 Tesla MRI Combined With Semiautomatic Segmentation for Differential Cortical and Medullary Assessment - Hammon, Matthias; Janka, Rolf Matthias; Siegl, Christian; Seuß, Hannes; Grosso, Roberto; Martirosian, Petros; Schmieder, Roland; Uder, Michael; Kistner, Iris (Medicine, 2016)
Magnetic resonance imaging with arterial spin labeling (ASL) is a noninvasive approach to measure organ perfusion. The purpose of this study was to evaluate the reproducibility of ASL kidney perfusion measurements with semiautomatic segmentation, which allows separate quantification of cortical and medullary perfusion.The right kidneys of 14 healthy volunteers were examined 6 times on 2 occasions (3 times at each occasion). There was a 10-minute pause between each examination and a 14-day interval between the 2 occasions. Cortical, medullary, and whole kidney parenchymal perfusion was determined with customized semiautomatic segmentation software. Coefficient of variances (CVs) and intraclass correlations (ICCs) were calculated.Mean whole, cortical, and medullary kidney perfusion was 307.26 ± 25.65, 337.10 ± 34.83, and 279.61 ± 26.73 mL/min/100 g, respectively. On session 1, mean perfusion for the whole kidney, cortex, and medulla was 307.08 ± 26.91, 336.79 ± 36.54, and 279.60 ± 27.81 mL/min/100 g, respectively, and on session 2, 307.45 ± 24.65, 337.41 ± 33.48, and 279.61 ± 25.94 mL/min/100 g, respectively (P > 0.05; R = 0.60/0.59/0.54). For whole, cortical, and medullary kidney perfusion, the total ICC/CV were 0.97/3.43 ± 0.86%, 0.97/4.19 ± 1.33%, and 0.96/4.12 ± 1.36%, respectively. Measurements did not differ significantly and showed a very good correlation (P > 0.05; R = 0.75/0.76/0.65).ASL kidney measurements combined with operator-independent semiautomatic segmentation revealed high correlation and low variance of cortical, medullary, and whole kidney perfusion.
EVALuna2:3854

Scanned versus Fused-Reconstructed Oblique MR-Images for Assessment of the Tibiofibular Syndesmosis-Diagnostic PerFormance and Reader Agreement - Seuß, Hannes; Hammon, Matthias; Roemer, Frank; Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Dankerl, Peter (Diagnostics, 2021)
To evaluate the diagnostic performance and reader agreement of a novel MRI image fusion method enabling the reconstruction of oblique images for the assessment of the tibiofibular syndesmosis. We evaluated 40 magnetic resonance imaging examinations of patients with ankle sprains (16 with ruptures and 24 without) for the presence of anteroinferior tibiofibular ligament rupture. For all patients, we performed a fusion of standard two-dimensional transversal and coronal 3 mm PDw TSE images into an oblique-fusion reconstruction (OFR) and compared these against conventionally scanned oblique sequence for the evaluation of the tibiofibular syndesmosis. To evaluate diagnostic performance, two expert readers independently read the OFR images twice. We analyzed sensitivity, specificity, negative and positive predictive values, accuracy, and agreement. Reader 1 misinterpreted one OFR as a false negative, demonstrating a sensitivity of 0.94 and specificity of 1.00, reader 2 demonstrated perfect accuracy. Intrareader agreement was almost perfect for reader 1 (alpha = 0.95) and was perfect for reader 2 (alpha = 1.00). Additionally, interreader agreement between all fusion sequence reads was almost perfect (alpha = 0.97). The proposed OFR enables reliable detection of anteroinferior tibiofibular ligament rupture with excellent inter- and intrareader agreement, making conventional scanning of oblique images redundant and supplies a method to retroactively create oblique images, e.g., from external examinations.
CRIS-Team WoS Importer:2021-03-19

Semi-automated De-identification of German Content Sensitive Reports for Big Data Analytics - Seuß, Hannes; Dankerl, Peter; Ihle, Matthias; Grandjean, Andrea; Hammon, Rebecca; Kaestle, Nicola; Fasching, Peter; Maier, Christian; Christoph, Jan; Sedlmayr, Martin; Uder, Michael; Hammon, Matthias; et al. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose Projects involving collaborations between different institutions require data security via selective de-identification of words or phrases. A semi-automated de-identification tool was developed and evaluated on different types of medical reports natively and after adapting the algorithm to the text structure. Materials and Methods A semi-automated de-identification tool was developed and evaluated for its sensitivity and specificity in detecting sensitive content in written reports. Data from 4671 pathology reports (4105 + 566 in two different formats), 2804 medical reports, 1008 operation reports, and 6223 radiology reports of 1167 patients suffering from breast cancer were de-identified. The content was itemized into four categories: direct identifiers (name, address), indirect identifiers (date of birth/operation, medical ID, etc.), medical terms, and filler words. The software was tested natively (without training) in order to establish a baseline. The reports were manually edited and the model re-trained for the next test set. After manually editing 25, 50, 100, 250, 500 and if applicable 1000 reports of each type re-training was applied. Results In the native test, 61.3 % of direct and 80.8 % of the indirect identifiers were detected. The performance (P) increased to 91.4 % (P25), 96.7 % (P50), 99.5 % (P100), 99.6 % (P250), 99.7 % (P500) and 100 % (P1000) for direct identifiers and to 93.2 % (P25), 97.9 % (P50), 97.2 % (P100), 98.9 % (P250), 99.0 % (P500) and 99.3 % (P1000) for indirect identifiers. Without training, 5.3 % of medical terms were falsely flagged as critical data. The performance increased, after training, to 4.0 % (P25), 3.6 % (P50), 4.0 % (P100), 3.7 % (P250), 4.3 % (P500), and 3.1 % (P1000). Roughly 0.1 % of filler words were falsely flagged. Conclusion Training of the developed de-identification tool continuously improved its performance. Training with roughly 100 edited reports enables reliable detection and labeling of sensitive data in different types of medical reports. Key Points: · Collaborations between different institutions require de-identification of patients' data. · Software-based de-identification of content-sensitive reports grows in importance as a result of 'Big data'. · A de-identification software was developed and tested natively and after training. · The proposed de-identification software worked quite reliably, following training with roughly 100 edited reports. · A final check of the texts by an authorized person remains necessary. Citation Format · Seuss H, Dankerl P, Ihle M et al. Semi-automated De-identification of German Content Sensitive Reports for Big Data Analytics. Fortschr Röntgenstr 2017; 189: 661 - 671.
EVALuna2:14623

Three-dimensional mapping of the arteriovenous loop model using two-dimensional histological methods - Seuß, Hannes; Arkudas, Andreas; Hammon, Matthias; Bleiziffer, Oliver; Uder, Michael; Horch, Raymund E.; Yuan, Quan (Microscopy Research and Technique, 2016)
The aim of this study was to create an analytical tool for the three-dimensional distribution of immunohistochemically stained cells in the arteriovenous (AV) loop model of the femoral vessels of rats that fuses two-dimensional histological slides into stacks.A total of 22 AV loops were implanted into male syngeneic Lewis rats by creating an arteriovenous fistula between the femoral artery and vein by interposing a femoral vein graft of the contralateral extremity. This fistula was embedded into an isolation chamber filled with a fibrin matrix. Specimens were explanted after 7 to 14 days, and the AV loop was processed using standard histological protocols. Immunohistochemical staining for HIF-1? and a counter staining with hematoxylin was performed. Various layouts with different cutting planes, regions of interest, and post-processing algorithms were evaluated. Results and observations: The proximal-to-distal cutting perpendicular to the vascular axis proved to be the best layout for mapping the three-dimensional constructs containing the AV loop. A semi-automatic algorithm for the differentiation of immunohistochemical positive and negative cells was developed.The newly established methods from this study constitute an excellent tool for the general evaluation of the AV loop model - particularly with regard to the three-dimensional distribution of immunohistochemical positive and negative cells.
EVALuna2:14606

Usability and Suitability of the Omics-Integrating Analysis Platform tranSMART for Translational Research and Education - Christoph, Jan; Knell, Christian; Boßerhoff, Anja Katrin; Naschberger, Elisabeth; Stürzl, Michael; Rübner, Matthias; Seuß, Hannes; Ruh, Manuel; Prokosch, Hans-Ulrich; Sedlmayr, Brita (Applied Clinical Informatics, 2017)
Platforms like tranSMART assist researchers in analyzing clinical and corresponding omics data. Usability is an important, yet often overlooked, factor affecting the adoption and meaningful use. Analyses on the specific needs of translational researchers and considerations about the application of such platforms for education are rare. The aim of this study was to test whether tranSMART can be used in education and how well medical students and professional researchers can handle it; to identify which kind of translational researchers-in terms of skills, experienced limitations, and available data-can take advantage of tranSMART; and to evaluate the usability and to generate recommendations for improvements. An online-based test has been done by medical students (N = 109) and researchers (N = 26). The test comprised 13 tasks in the context of four typical research scenarios based on experimental and clinical data. A web questionnaire was provided to identify both the needs and the conditions of research as well as to evaluate the system's usability based on the "System Usability Scale" (SUS). Students and researchers were able to handle tranSMART well and coped with most scenarios: cohort identification, data exploration, hypothesis generation, and hypothesis validation were answered with a rate of correctness between 82 and 100%. Of the total, 72.2% of the teaching researchers considered tranSMART suitable for their lessons and 84.6% of the researchers considered the platform useful for their daily work; 65.4% of the researchers named the nonavailability of a platform like tranSMART as a restriction on their research. The usability was rated "acceptable" with a SUS of 70.8. tranSMART is potentially suitable for education purposes and fits most of the needs of translational researchers. Improvements are needed on the presentation of analysis results and on the guidance of users through the analysis, especially to ensure the compliance of the analysis with the requirements of statistical testing.
EVALuna2:195

Vascularization of the Arteriovenous Loop in a Rat Isolation Chamber Model-Quantification of Hypoxia and Evaluation of Its Effects - Yuan, Quan; Arkudas, Andreas; Horch, Raymund E.; Hammon, Matthias; Bleiziffer, Oliver; Uder, Michael; Seuß, Hannes (Tissue Engineering: Parts A, B, and C, 2017)
The aim of this study was to analyze the three-dimensional distribution of hypoxia in the arteriovenous (AV) loop model in rats, by examining the distribution of hypoxia-inducible factor-1 alpha (HIF-1?).AV loops were created from the femoral artery and vein of male Lewis rats and an interpositional graft from the contralateral femoral vein. This AV fistula was embedded in a fibrin-filled isolation chamber and subcutaneously implanted into the thigh. The specimens were harvested after 7 days (n = 4), 10 days (n = 5), and 14 days (n = 4). The fibrin clots were stained for lectin, HIF-1?, and ectodysplasin 1 (ED1). The distribution of positive and negative cells was analyzed in three dimensions and at different points in time.The HIF-1?-positive rate increased from the proximity of the central vessel to the distant regions. From day 7 to 10, we noted a decrease in the HIF-1?-positive rate in the proximity of the vessels and an increase in the periphery. A global decrease in positive cells was seen at day 14. HIF-1? and macrophage (ED1) double staining indicated that macrophages accounted for a significant fraction of the cells. Double staining for endothelium (with lectin) demonstrated that no HIF-1? was detectable in well-vascularized areas.In the AV loop model, the HIF-1?-positive cell distribution is highly related to the vascularization process. The onset of rapid vessel outgrowth follows the increase of the HIF-1? rate closely, indicating that HIF-1? may be a driving force for vascularization.
EVALuna2:14719

Virtual Computed Tomography Colonography: Evaluation of 2D and Virtual 3D Image Quality of Sub-mSv Examinations Enabled by Third-generation Dual Source Scanner Featuring Tin Filtering - Seuß, Hannes; Janka, Rolf Matthias; Hammon, Matthias; Uder, Michael; Dankerl, Peter; Cavallaro, Alexander Josef (Academic Radiology, 2018)
RATIONALE AND OBJECTIVES: To evaluate two- and three-dimensional (2D and 3D) image quality of sub-milliSievert (mSv) computed tomography (CT) colonography utilizing a third-generation dual source CT scanner featuring a tin filter. METHODS: We retrospectively evaluated 26 consecutive patients who underwent third-generation dual source CT colonography, nine with the standard-dose clinical-scan protocol (SDP) and 17 with a low-dose protocol (LDP) featuring a tin filter. Radiation dose was evaluated by volume computed tomography dose index (CTDIvol), dose length product (DLP), effective dose (E), and size-specific dose estimate. Objective image quality was evaluated utilizing signal-to-noise ratio (SNR) derived from standardized placed regions of interest on the transverse 2D images and the ratio of SNR/CTDIvol (normalized SNR). Two radiologists in consensus assessed subjective image quality of the virtual 3D images. RESULTS: There were no significant differences in subjective image quality (P = .661). All examinations were rated "excellent" or "good" for diagnostic confidence. The mean total for DLP/E was 143.4 ± 29.8 mGy/3.00 ± 0.40 mSv in the SDP and therefore significantly higher than in the LDP with 36.9 ± 8.7 mGy/0.75 ± 0.16 mSv (P < .001). The SNR was 8.9 ± 2.1 in the SDP and 4.9 ± 0.8 in the LDP. CONCLUSIONS: Third-generation dual source CT featuring a tin filter enables consistent sub-mSv colonography without substantially impairing image quality.
EVALuna2:34692